A trauma-informed care model for HIV prevention and care for refugee women in the United States: perspectives and implementation framework - Nkodo, Emmanuel Nazaire Essam; Fadul, Nada (Frontiers in Medicine, 2025)
HIV disproportionately impacts women, particularly in sub-Saharan Africa and other low-and middle-income countries, where conflict and displacement heighten their vulnerability to HIV. Refugee women face compounded challenges, including trauma before and during migration and healthcare inequities in host countries. This perspective paper aims to assess existing evidence on HIV treatment and prevention for refugee women resettling in the U.S., using intersectional stigma and the status-neutral service delivery model as theoretical frameworks, to propose an implementation strategy. Trauma-informed care (TIC) offers a promising approach to address these challenges, emphasizing culturally responsive, safe, and empowering healthcare. Integrating TIC with the status-neutral model, which centers on HIV testing and pathways for prevention or treatment, can improve care access and outcomes. Moreover, including refugee women and stakeholders in designing tailored interventions that address individual and systemic-level barriers is critical to fostering health equity.